Depression and Associated Factors in Patients with Implantable Cardioverter-Defibrillators - Maryam Moshkani Farahani; Mehrdad Taghipour; Mohsen Motalebi; Ramezan Bakhshian; Ramezan Bakhshian; Ehsan Shahverdi; Sovaid Taghipour; Soheyla Abdi; Ramzan Moradi (Journal of Tehran University Heart Center, 2017)
Background: Psychological problems such as depression constitute a dilemma that patients with the implantable cardioverter-defibrillator (ICD) usually encounter and may impact their quality of life. The purpose of this study was to evaluate the prevalence of depression among adults with the ICD and the relationship between depression and associated factors.